Intet nyt under solen: Strategier for hverdagsæstetiske kurateringspraksisser - Jantzen, Christian (Academic Quarter | Akademisk kvarter, 2019)
Aestheticization is nothing new under the sun. Potentially, all texts – even instructional ones – may function in an aesthetic way, because aesthetics relate to the expressive dimension of messages and all verbal messages consist of this dimension. The purpose of this article is to use insights from literary studies, more specifically from structuralism, to understand how people curate their own way of life in late modern society. The core question is: Which strategies do people use when aestheticizing their life? And the answer is: Approximately the same strategies as those utilized in aesthetic or aestheticized texts. Such strategies are identified in an analysis of two sentences. The analysis explores the aesthetic principles at work in these sentences and the strategies these principles serve: i.e. embellishment and estrangement. In the concluding discussion, these two strategies are discussed in relation to everyday aesthetics, and a third strategy is identified: aesthetic evolution.